2019
DOI: 10.1111/jfd.12968
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a diagnostic procedure in surveillance of the listed fish diseases IHN and VHS

Abstract: Infectious haematopoietic necrosis (IHN) and viral haemorrhagic septicaemia (VHS) are OIE‐listed and notifiable viral fish diseases which are controlled by eradication and surveillance programmes globally. The present study provides improved RT‐qPCR procedures based on recently described OIE protocols. Improvements comprise the design of a new TaqMan® probe, replacing a TaqMan® MGB probe that turned out to show impaired binding. Reason for this is SNPs detected in the nucleoprotein N gene sequences of IHNV str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…All three of these isolates were obtained from Idaho rainbow trout farms, an industry and region associated with unusually high rates of IHNV genetic diversity [ 32 , 33 ]. In Germany, reduced sensitivity has been reported for the N Uni RT-rPCR when detecting E genogroup isolates associated with the rainbow trout industry due to the presence of nucleotide substitutions in the probe region [ 34 ]. A redesigned probe, implemented as a one-step PCR protocol, showed improved sensitivity for a limited number of German E isolates of IHNV tested in the study.…”
Section: Discussionmentioning
confidence: 99%
“…All three of these isolates were obtained from Idaho rainbow trout farms, an industry and region associated with unusually high rates of IHNV genetic diversity [ 32 , 33 ]. In Germany, reduced sensitivity has been reported for the N Uni RT-rPCR when detecting E genogroup isolates associated with the rainbow trout industry due to the presence of nucleotide substitutions in the probe region [ 34 ]. A redesigned probe, implemented as a one-step PCR protocol, showed improved sensitivity for a limited number of German E isolates of IHNV tested in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The viral culture needs too much time for isolating and authenticating. Moreover, there is no sensitive cell lines for some viruses of aquatic animals [2,4] . Enzyme-linked immunosorbent assay (ELISA) is the most typical immunological method, which could detect virus antigen or antibody.…”
Section: Salmonids Viral Diseases Detection Developmentsmentioning
confidence: 99%
“…The RT-LAMP methods were also successfully developed to detect the IPNV [20,34,37] . Rodriguez et al [4] evaluated the five serological methods and RT-PCR and found that RT-PCR were the most appropriate and sensitive methods for the routine detection of IPNV from affected fish. Therefore, the nucleic acid test is the most commonly used detection method in the diagnosis of aquaculture viral pathogens.…”
Section: Salmonids Viral Diseases Detection Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RT-qPCR of IHNV and VHSV samples were performed using a RT-qPCR kit (iTaq universal probes one-step kit, Bio-Rad) according to Chico et al (2006) and Hoferer et al (2019), respectively, and the protocols recommended by the Bavarian State Office for Health and Food Safety (LGL). As the negative control nuclease-free water was used and extraction and amplification controls were prepared using intype IC-RNA (Indical Bioscience GmbH) and specific primers and probe (Sigma-Aldrich).…”
Section: Determination Of Titre and Genomic Materials Of The Target mentioning
confidence: 99%